Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines on the Role of Steroids in the Treatment of Adults With Metastatic Brain Tumors. Issue 3 (9th January 2019) - Ryken, Timothy C; Kuo, John S; Prabhu, Roshan S; Sherman, Jonathan H; Kalkanis, Steven N; Olson, Jeffrey J
Abstract: QUESTION: Do steroids improve neurological symptoms and/or quality of life in patients with metastatic brain tumors compared to supportive care only or other treatment options? If steroids are given, what dose should be used? TARGET POPULATION: These recommendations apply to adults diagnosed with brain metastases. RECOMMENDATIONS:  STEROID THERAPY VERSUS NO STEROID THERAPY Asymptomatic brain metastases patients without mass effect Insufficient evidence exists to make a treatment recommendation for this clinical scenario. Brain metastases patients with mild symptoms related to mass effect Level 3: Corticosteroids are recommended to provide temporary symptomatic relief of symptoms related to increased intracranial pressure and edema secondary to brain metastases. It is recommended for patients who are symptomatic from metastatic disease to the brain that a starting dose of 4 to 8 mg/d of dexamethasone be considered. Brain metastases patients with moderate to severe symptoms related to mass effect Level 3: Corticosteroids are recommended to provide temporary symptomatic relief of symptoms related to increased intracranial pressure and edema secondary to brain metastases. If patients exhibit severe symptoms consistent with increased intracranial pressure, it is recommended that higher doses such as 16 mg/d or more be considered. CHOICE OF STEROID: Level 3: If corticosteroids are given, dexamethasone is the best drug choice given the available evidence. Duration of Corticosteroid Administration Level 3: Corticosteroids, if given, should be tapered as rapidly as possible but no faster than clinically tolerated, based upon an individualized treatment regimen and a full understanding of the long-term sequelae of corticosteroid therapy. Given the very limited number of studies (2) which met the eligibility criteria for the systematic review, these are the only recommendations that can be offered based on this methodology. The full guideline can be found at https://www.cns.org/guidelines/guidelines-treatment-adults-metastatic-brain-tumors/chapter_7 .